Chronic upper airway and systemic inflammation from copier emitted particles in healthy operators at six Singaporean workplaces - Bello, Dhimiter; Chanetsa, Lucia; Christophi, Costas A.; Poh, Tuang Yeow; Singh, Dilpreet; Setyawati, Magdiel Inggrid; Christiani, David C.; Chotirmall, Sanjay H.; Ng, Kee Woei; Demokritou, Philip (My University, 2021)
Toner-based printing equipment (TPE), including laser printers and photocopiers, utilize several engineered nanomaterials (ENMs) to improve toner performance. Operation of TPE, which rarely employ any exposure controls, generates high exposures to nanoparticles that contain ENMs and complex organics. Epidemiological literature in copier operators documents respiratory effects, including nasal blockage, cough, excessive sputum, and breathing difficulties, cardiovascular effects, oxidative stress, and inflammation. However, epidemiological studies in humans with adequate exposure assessment and dose-response analysis are lacking. We present herein the analysis of the upper airway and systemic inflammation in plasma of 19 healthy copier operators at six Singapore workplaces. We employed a repeated panel design (four biomarker measurements over two weeks) combined with a multi-marker approach (14 inflammatory cytokines in plasma and nasal lavage (NL)), and comprehensive exposure assessment using four distinct exposure metrics. We investigated spatial and temporal patterns of markers of upper airway and systemic inflammation and their association with various exposure metrics. Several inflammatory markers, namely fractalkine, IL-1β, and IL-1α in NL, and fractalkine, IL-1β, TNF-α, and IFN-γ in plasma, were strongly and positively associated with at least one exposure metric, whereas GM-CSF was negatively associated. The inflammation score was also strongly associated with TPE nanoparticle exposures. Exposure to TPE emissions induced moderate upper airway inflammation and stronger systemic inflammation in these healthy operators, characterized by upregulation of at least IL-1β, fractalkine, TNF-α and IFN-γ. Proinflammatory cytokines TNF-α, IFN-γ and IL-1β play an important role in orchestrating inflammatory responses in various clinical conditions, including cardiovascular and autoimmune disease, and likely trigger activation of endothelial cells, leading to overexpression of fractalkine, a chemokine that is involved in and associated with multiple disorders, including atherosclerosis and vascular disease. Future larger-scale epidemiological studies in these workers and consumers exposed chronically to TPE nanoparticle emissions and proactive interventions to reduce or eliminate TPE exposures are recommended.
Keywords: Biomarkers; Engineered nanoparticles; Fractalkine; IL-1β, IFN-γ; Inflammation; Occupational health; Printers and photocopiers; TNF-α